The impact of democratic philosophy on the axes of interests considered criminalization - Hilal Hwaidi Al-Zaidi, Researcher. Umalbaneen; Hammad Hameed Al-Hamad, Prof. Dr. Hasan (Basra studies journal, 2024)
The penal texts that make up the penal law as a whole include penal legal rules, and that these rules contain content, which is the essence or purpose of the rule, which is known as interest. Since the legislator does not legislate a text without basing it on an interest that he protects through this text, whether this text is related to political, economic or social affairs, Thus, interest becomes the criterion on which the criminal legislator relies in drawing up his philosophy to solve some legal problems. However, the interest subject to legal protection does not arise from a vacuum, but rather it is closely linked to the philosophy of the state, so what is considered an interest that requires protection under one philosophy is not considered so under another philosophy. As a result of the philosophical and political transformation that the Iraqi Republic witnessed after 2003, after it had a dictatorial philosophy, it became a democratic one.